Archetypes of Digital Twins - Hendrik van der Valk; Hendrik Haße; Frederik Möller; Boris Otto (Business & Information Systems Engineering, 2021)
Currently, Digital Twins receive considerable attention from practitioners and in research. A Digital Twin describes a concept that connects physical and virtual objects through a data linkage. However, Digital Twins are highly dependent on their individual use case, which leads to a plethora of Digital Twin configurations. Based on a thorough literature analysis and two interview series with experts from various electrical and mechanical engineering companies, this paper proposes a set of archetypes of Digital Twins for individual use cases. It delimits the Digital Twins from related concepts, e.g., Digital Threads. The paper delivers profound insights into the domain of Digital Twins and, thus, helps the reader to identify the different archetypical patterns.
Keywords: 000; Digital Twin; Archetypes; Dimensions; Characteristics; Cluster analysis